Uncommon Complication of Uterine Artery Embolization: Expulsion of Infarcted Myoma and Uterine Sepsis - Juliana G. Martins; Dawn Gaudenti; Frank Crespo; Dervi Ganesh; Usha Verma (Hindawi Limited, 2016)
Uterine leiomyomas are the most common benign tumors in young females and leading cause of hysterectomy. Uterine artery embolization is a safe option for women who wish to retain their uterus. Several complications have been reported including expulsion and sepsis. MRI is a useful pretreatment tool to predict results and outcomes. We report a case of a 44-year-old female with a history of uterine fibroids with the largest one being intracavitary. Patient underwent uterine artery embolization that was complicated by endomyometritis that failed antibiotics, leading to sepsis and hysterectomy.